2019
DOI: 10.1186/s12864-019-5555-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and pathogenicity potential of members of the Pseudomonas syringae species complex on Prunus spp

Abstract: Background Diseases on Prunus spp. have been associated with a large number of phylogenetically different pathovars and species within the P. syringae species complex. Despite their economic significance, there is a severe lack of genomic information of these pathogens. The high phylogenetic diversity observed within strains causing disease on Prunus spp. in nature, raised the question whether other strains or species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 101 publications
(125 reference statements)
2
46
0
Order By: Relevance
“…The citrus- P. syringae pathosystem is complex as shown previously on Prunus species. Ruinelli et al ( 2019 ) found that a large number of various P. syringae strains are pathogenic on the tested hosts (cherry, peach and almond). Similarly Parisi et al ( 2019 ), isolated four phylogroups (PG01, 02, 03 and 07) able to induce canker on apricot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The citrus- P. syringae pathosystem is complex as shown previously on Prunus species. Ruinelli et al ( 2019 ) found that a large number of various P. syringae strains are pathogenic on the tested hosts (cherry, peach and almond). Similarly Parisi et al ( 2019 ), isolated four phylogroups (PG01, 02, 03 and 07) able to induce canker on apricot.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Parisi et al ( 2019 ), isolated four phylogroups (PG01, 02, 03 and 07) able to induce canker on apricot. Ruinelli et al ( 2019 ) suggest the diversity of strains pathogenic on Prunus is probably due to independent evolution of individual strains, not necessarily related to virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, sampling studies have indicated that the different pathogens commonly coexist within orchards, nurseries, and forests (Vicente et al, 2004;Gilbert et al, 2008;Kałużna et al, 2010). (Gilbert et al, 2008;Bultreys and Kałużna, 2010;Hulin et al, 2018a;Parisi et al, 2019;Ruinelli et al, 2019). Psm R1 and R2 have evolved within woody host-infecting clades of phylogroups 3 and 1, respectively (Nowell et al, 2016).…”
Section: Phylog Ene Tic S Re Ve Al S Converg Ent E Volutionmentioning
confidence: 99%
“…To understand how each of the different clades have evolved virulence on cherry, genomic analysis allowed the identification of the sets of genes encoding T3Es and toxin and hormone biosynthesis (Hulin et al, 2018a;Ruinelli et al, 2019;Marcelletti and Scortichini, 2019).…”
Section: What Mak E S a Cherry Pathog En?mentioning
confidence: 99%